(untitled) (Maneggio, 2025)
This study aims to examine the influence of transformational leadership on employee performance using a human resource management approach. Transformational leadership, which includes idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, is believed to enhance employee motivation, innovation, and commitment in achieving organizational goals. The research method employed a quantitative approach through a survey of 150 employees in the service industry sector. Data were analyzed using multiple linear regression to test the relationship between transformational leadership variables and employee performance. The results indicate that transformational leadership has a positive and significant effect on employee performance. These findings highlight the importance of the role of human resource management in developing and implementing transformational leadership styles through training and supportive reward systems. This research provides practical contributions for organizations to improve performance and foster an adaptive and innovative work culture.